Pengaruh Beban Kerja dan Burnout terhadap Capaian Kinerja Pegawai dengan Mental Health sebagai Variabel Intervening pada Kantor Pelayanan Pajak Pratama Jember - Angelia Arisca Yuliarto; Budi Santoso; angelia@gmail.com (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of workload and burnout on employee performance achievement with mental health as an intervening variable at the Jember Pratama Tax Service Office. The research method used is a quantitative approach with a census technique on 93 employees, and data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through WarpPLS 8.0. The results of the study indicate that workload and burnout have a positive and significant effect on mental health, workload has a positive and significant effect on employee performance, burnout has no significant direct effect on performance, and mental health has a positive and significant effect on performance. In addition, mental health is proven to mediate the effect of workload on performance partially and mediate the effect of burnout on performance fully. The conclusion is that mental health is a key mechanism in bridging the influence of workload and burnout on employee performance achievement, so that proportional workload management and burnout prevention need to be accompanied by strengthening mental health programs to improve organizational performance sustainably. Keywords: Workload, Burnout, Mental Health, Employee Performance